Physiological Response of Haloxylon ammodendron Seedlings to Drought Stress Under Different Levels of Nitrogen Application - Yaxin SHI; Ze WANG; Cai REN; Hanhan ZHENG; Cong ZHOU; Fan QI (Guangdong nongye kexue, 2024)
【Objective】It aims to explore the response of different nitrogen fertilizer levels to the growth and physiological changes of Haloxylon ammodendron seedlings under drought stress, and to provide theoretical basis and technical parameters for ecological restoration and vegetation conservation management in desert areas.【Method】The H.